A case for considering age and sex when prescribing rest intervals in resistance training - Grgic, J.; Schoenfeld, B. J. (Kinesiology, 2019)
Current resistance training position stands recommend that rest interval duration in resistance training should be prescribed based on the training goal and exercise selection. However, these recommendations are mostly extrapolated from studies that included young men as participants. Therefore, they cannot be generalized to all age groups and all resistance training programs. Herein, two overlooked, but possibly important factors for rest interval prescription are discussed: (1) age, and (2) sex of the individual. Acute studies indicate that older adults, as compared to young adults, require a shorter duration rest interval to achieve recovery between sets. Due to the sex differences in fatigability, it can be speculated that men need a longer duration rest interval than women to maintain high levels of performance. Both sex and age may be relevant variables when determining rest interval duration in resistance exercise and should not be overlooked by exercise practitioners in program design.